DAMAI Model as a Prototype of Religious Moderation - Labobar, Kresbinol (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
The first principle of Pancasila states that Indonesia as a nation that believes in God Almighty. Although Indonesia is officially secular, it is a diverse nation in terms of culture and religion. This diversity presents the possibility of disputes arising from religious matters in different areas. This article emphasizes how elements like the politicization of religion, exclusivism, and identity politics may lead to religious insecurity. The use of the DAMAI paradigm (Dialogue, Adaptation, Mediation, Accommodation, Integration) to build religious moderation in the context of Christian theological education in Papua is also covered in this article. Descriptive qualitative research methodology is employed in this study. Forty participants—representing staff, instructors, and students—were interviewed, and observations were made in order to gather data. The study’s findings demonstrate the high degree of DAMAI model application at Sentani State Protestant Christian College (STAKPN Sentani), with scores ranging from 80% to 99% for indicators including Communication, Justice, Love, Security, and Innovation. The DAMAI paradigm is presented in this article to foster inclusive and peaceful religious moderation in Papua while shedding light on the challenges related to religious moderation in Christian theological education settings.